2005
DOI: 10.2134/agronj2004.0287
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Soil Nitrogen Parameters Related to Soil Texture and Corn Yield

Abstract: The spatial variability of soil properties that affect the soil N budget and corn (Zea mays L.) grain yield were studied for 2 yr in south‐central Texas to better assess the potential for variable‐rate N fertilization. Residual soil NO3–N with depth and soil N mineralization (Nmin) potential and their relationships with soil total N, soil organic C, and clay content were characterized. Residual soil NO3–N to 60‐cm depth was more related to corn yield than NO3–N at shallower depths. Residual soil NO3–N showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…Another major factor contributing to low NUE in current strategies has been uniform application rates of fertilizer N to spatially variable landscapes, even though numerous field studies have indicated economic and environmental justification for spatially variable N applications in many agricultural landscapes (Mamo et al, 2003;Hurley et al, 2004;Koch et al, 2004;Scharf et al, 2005;Shahandeh et al, 2005;Lambert et al, 2006;Hong et al, 2007). Uniform applications within fields discount the fact that N supplies from the soil, crop N uptake, and response to N are not the same spatially (Inman et al, 2005).…”
Section: Causes Of Low Nue For Current N Management Strategiesmentioning
confidence: 99%
“…Another major factor contributing to low NUE in current strategies has been uniform application rates of fertilizer N to spatially variable landscapes, even though numerous field studies have indicated economic and environmental justification for spatially variable N applications in many agricultural landscapes (Mamo et al, 2003;Hurley et al, 2004;Koch et al, 2004;Scharf et al, 2005;Shahandeh et al, 2005;Lambert et al, 2006;Hong et al, 2007). Uniform applications within fields discount the fact that N supplies from the soil, crop N uptake, and response to N are not the same spatially (Inman et al, 2005).…”
Section: Causes Of Low Nue For Current N Management Strategiesmentioning
confidence: 99%
“…Soil texture also influences N dynamics and crop uptake as a result of its influence on soil physical properties such as K sat on water availability and biological activity (e.g., denitrification, mineralization, and immobilization). Shahandeh et al (2005) found that soil clay content was negatively correlated with corn yield; however, clay content was also found to be positively related to N mineralization and soil organic carbon levels. Hence, the relationship between clay content, N mineralization, and crop growth can be very complicated.…”
Section: Corn Grain Nitrogen Uptakementioning
confidence: 93%
“…1-5), it appears that some of the applied N must have been immobilized and then mineralized during the subsequent growing season for us to observe an N response to fall fertilizer N application. Shahandeh et al (2005) reported that corn yield in south central Texas was related more strongly to the amount of residual soil NO 3 − -N over the entire primary rooting depth (top 60 cm) than to NO 3 − -N amounts at shallower depths. In this study, N uptake by corn (fall 2008) likely responded to the combined effects of residual N left over from the previous year's N addition (fall 2007), background soil N resulting from the mineralization of soil organic N, and recently applied N that was immobilized and then remineralized during the following growing season.…”
Section: Corn Grain Nitrogen Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…The main causes for the low efficiency of corn N fertilization are: high losses by N-NH 3 volatilization (Lara Cabezas et al, 1997b;Cantarella et al, 2008), N-NO 3 -leaching (Sangoi et al, 2003;Ceretta et al, 2005), lack of synchrony between crop demand and N availability (Amado et al, 2002;Aita & Giacomini, 2008), inter-annual variability in the crop response to N fertilization (Fiorin et al, 2007;Ciampitti & Garcia, 2008), and spatial variability of soil organic matter (SOM) and N mineralization potential (Shahandeh et al, 2005;Gregoret et al, 2006;Solie et al, 1999;Casa et al, 2011;Portz et al, 2012). All these factors influence N fertilization, making an increase in fertilizer use efficiency a complex challenge.…”
Section: Introductionmentioning
confidence: 99%